Escala de Macarthur de status social subjetivo: validade e associação com indicadores de posição socioeconômica no curso de vida - estudo longitudinal de saúde do adulto (ELSA-BRASIL) - Wasney de Almeida Ferreira (2016)
INTRODUCTION: The MacArthur scale of subjective social status (SSS), which combines verbal instruction and an image of a 10-steps ladder, aims to capture the common sense perception that an individual has about his/her own position in social hierarchies, in three different contexts: society, community and work. OBJECTIVE: To conduct a concurrent and face validity analysis of the MacArthur scale (Paper 1) and to investigate whether individuals who perceive themselves as having a low SSS in adult life, in the society context, were more exposed to low objective socioeconomic positions (SEP) in childhood and youth, after adjusting for current SEP. METHODS: The article 1 included 159 participants from the Longitudinal Study of Adult Health (ELSA-Brasil), from Minas Gerais Investigating Center, selected by convenience during the 2nd wave of interviews and examinations between 11/2012 and 02/2014. The MacArthur scale was compared with a Status scale, created for this study based on the cognitive metaphor theory, which used the same image of a ladder as an indicator of the status and a very similar but more direct instruction. The concurrent validity was examined by comparing the answers to both scales (MacArthur and Status) using weighted kappa statistics. The face validity was assessed by qualitative methods from corpus linguistics. Ordinal logistic regression was used to investigate whether sociodemographic factors were associated with differences of 1, or 2 or more steps in the choices made using the MacArthur and the Status ladders. In the paper 2, 15.105 participants from the base line of ELSA-Brasil (2008-2010) were included. Low SSS was in the society was defined by the choice of a step lower than 5 out of 10. Multivariate logistic regression analysis was used to investigate whether exposures to low objective indicators of SEP in the childhood (maternal education), youth (occupational social class of the household head; occupational social class of the first job; nature of occupation of household head; nature of occupation in the first job) and adult life (current occupational social class; current nature of occupation; current education) increased the chances of being at low SSS. RESULTS: Agreement between the answers to the MacArthur and Status scales moderated in the society context (kw=0,55) and good in the community (kw=0,60) and work (kw=0,67). Face validity analysis showed that MacArthur scale captures beyond the classic socioeconomic indicators, encompassing elements from collective health, as home, transport, health, leisure, merit etc. Although individuals without college education (in the society context) and women (in the community ambience) had greater chances of differing by 1, or 2 or more steps from those with college education or who were women, qualitative differences were not identified by the corpus linguistics, suggesting that the MacArthur scale has good face validity. In paper 2, after adjustments, low SSS in adult life remained statistically associated with low SEP in all stages of the life course, being the magnitude of the associations strong in adult life, moderate in youth and weak in childhood, showing dose response gradients in all associations. CONCLUSION: The MacArthur scale seems to be a valid instrument to measure the SSS in the Brazilian sociocultural context, thus they can be used in studies of social inequality in health. In addition, results suggest that the scale may capture a summary of exposures and experiences of present and past SEP, both intra and intergenerational, allowing to expand the interpretations of findings of health inequalities based on the MacArthur scale.